2008
DOI: 10.1111/j.1600-0838.2007.00709.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility and changes in twitch properties associated with age and resistance training in young and elderly women

Abstract: We compared knee extensor twitch contractile properties (TP) between nine young women (YW, 20-30 years) and 10 elderly women (63-78 years) and examined changes associated with resistance training in addition to measurement reproducibility. Data were obtained on two occasions 3 weeks apart after which subjects performed bilateral leg extension and bilateral leg curl exercises 3 days/week for 10 weeks. TP demonstrated moderate to good reproducibility in both age groups with Pearson's r and the intra-class correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…In addition, percent change from T Base was calculated and a one-sample t test against zero was conducted to provide additional assurance of the accuracy of baseline data (Table 1). In line with previous literature (Cannon et al 2008), all direct measures showed moderate to good reproducibility, with ICCs ranging from 0.67 to 0.99 and TEM ranging from 6.3% to 13.2%. Good reliability was also shown for the 3 CMJ variables (ICC, r = 0.77 to 0.98; TEM = 5.1% to 5.7%).…”
Section: Postural Sway Assessmentsupporting
confidence: 84%
“…In addition, percent change from T Base was calculated and a one-sample t test against zero was conducted to provide additional assurance of the accuracy of baseline data (Table 1). In line with previous literature (Cannon et al 2008), all direct measures showed moderate to good reproducibility, with ICCs ranging from 0.67 to 0.99 and TEM ranging from 6.3% to 13.2%. Good reliability was also shown for the 3 CMJ variables (ICC, r = 0.77 to 0.98; TEM = 5.1% to 5.7%).…”
Section: Postural Sway Assessmentsupporting
confidence: 84%
“…Although previous studies have reported the reliability of evoked and voluntary muscle actions separately (Place et al, 2007;Cannon et al, 2008), none have specifically compared the reliability of voluntary versus evoked muscle actions. Our study indicated that, except for TRTD V , voluntary and evoked measures of neuromuscular function are similarly consistent.…”
Section: Resultsmentioning
confidence: 99%
“…Force outputs were corrected for gravitation effects and torque values were quantified in relation to lever arm length during analyses using the methods of Cannon et al. ().…”
Section: Methodsmentioning
confidence: 99%
“…The MVC protocol involved 20 ¥ 5 s isometric efforts completed using a work-to-rest ratio of 1:1. Force outputs were corrected for gravitation effects and torque values were quantified in relation to lever arm length during analyses using the methods of Cannon et al (2008).…”
Section: Neuromuscular Functionmentioning
confidence: 99%